2015
DOI: 10.1002/eji.201445206
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of IL‐33 receptor ST2 in experimental cerebral malaria development

Abstract: were not affected in the absence of functional ST2 pathway, the local expression of ICAM-1, CXCR3, and LT-α, crucial for ECM development, was strongly reduced, and this may explain the diminished pathogenic T-cell recruitment and resistance to ECM. Therefore, IL-33 is induced in PbA sporozoite infection, and the pathogenic T-cell responses with local microvascular pathology are dependent on IL-33/ST2 signaling, identifying IL-33 as a new actor in ECM development. Keywords:Experimental cerebral malaria r IL-33 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 53 publications
1
38
0
Order By: Relevance
“…IL-33 is strongly expressed within the CNS [22], and we recently showed that the high steady-state levels of IL-33 protein found in naïve brain doubled during ECM, after blood stage or sporozoite Pb A-infection [11]. Since IL-33/ST2 has been implicated in Pb A-induced ECM, we first assessed the cellular source of IL-33 brain expression.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…IL-33 is strongly expressed within the CNS [22], and we recently showed that the high steady-state levels of IL-33 protein found in naïve brain doubled during ECM, after blood stage or sporozoite Pb A-infection [11]. Since IL-33/ST2 has been implicated in Pb A-induced ECM, we first assessed the cellular source of IL-33 brain expression.…”
Section: Resultsmentioning
confidence: 99%
“…As in humans, increased levels of inflammatory cytokines and chemokines are present in the brain of Plasmodium berghei ANKA ( Pb A) infected mice during experimental cerebral malaria (ECM) [10, 11]. We showed recently that IL-33 protein levels are increased in the brain undergoing ECM, and that mice deficient for IL-33 receptor ST2 display resistance to ECM after Pb A sporozoite or blood stage infection with a reduced ICAM expression and microvascular obstruction in the brain, and with decreased pathogenic T cell sequestration and LT-α induction [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies exist regarding IL-33 in other CNS conditions, including stroke Luo et al, 2015), neuropathic pain (Zarpelon et al, 2016;Liu et al, 2015), infection (Peng et al, 2013;Hudson et al, 2008;Palomo et al, 2015;Tong and Lu, 2015), and age related macular degeneration (Xi et al, 2016), but given a dearth of literature these will not be specifically discussed here.…”
Section: Il-33 In Cns Pathologymentioning
confidence: 99%